Association between nicotinic acetylcholine receptor single nucleotide polymorphisms and smoking cessation. - Spruell, T; Colavita, G; Donegan, T; Egawhary, M; Hurley, M; Aveyard, P; Johnstone, E; Murphy, M; Munafò, MR (Oxford University Press, 2012)
INTRODUCTION: The α4β2 nicotinic receptor is of central importance in tobacco dependence, while the homomeric α7 receptor may also play a role. In this candidate gene study, we examine the association between 8 single nucleotide polymorphisms (SNPs) in genes coding for nicotinic acetylcholine receptor subunits α4 (rs1044396, rs2273504, rs2236196, and rs2273502), α7 (rs2133965 and rs4779969), and β2 (rs2072660 and rs2072661) and smoking abstinence in a cohort of quitters enrolled in a clinical trial of behavioral support. METHODS: Data were obtained from the "Patch in Practice" study, involving 925 smokers in the United Kingdom. All participants were given an 8-week course of 15 mg of transdermal nicotine replacement therapy and blood was taken for genotyping. RESULTS: Logistic regression analyses assessed the association between each selected SNP and smoking abstinence at 4, 12, 26, and 52 weeks. There were no statistically significant associations with smoking cessation success or nicotine intake assessed by plasma cotinine levels. However, rs2273502 was associated with a consistent (though nonsignificant) increase in the odds of abstinence. CONCLUSIONS: There was no compelling evidence that these SNPs were associated with a reduced or higher chance of abstinence. However, rs2273502 may be worth investigating in future studies.